Solute stabilization of nanocrystalline tungsten against abnormal grain growth. Issue 1 (5th September 2017) - Donaldson, Olivia K.; Hattar, Khalid; Kaub, Tyler; Thompson, Gregory B.; Trelewicz, Jason R.
Abstract: Abstract : Microstructure and phase evolution in magnetron sputtered nanocrystalline tungsten and tungsten alloy thin films are explored through in situ TEM annealing experiments at temperatures up to 1000 °C. Grain growth in unalloyed nanocrystalline tungsten transpires through a discontinuous process at temperatures up to 550 °C, which is coupled to an allotropic phase transformation of metastable β-tungsten with the A-15 cubic structure to stable body centered cubic (BCC) α-tungsten. Complete transformation to the BCC α-phase is accompanied by the convergence to a unimodal nanocrystalline structure at 650 °C, signaling a transition to continuous grain growth. Alloy films synthesized with compositions of W–20 at.% Ti and W–15 at.% Cr exhibit only the BCC α-phase in the as-deposited state, which indicate the addition of solute stabilizes the films against the formation of metastable β-tungsten. Thermal stability of the alloy films is significantly improved over their unalloyed counterpart up to 1000 °C, and grain coarsening occurs solely through a continuous growth process. The contrasting thermal stability between W–Ti and W–Cr is attributed to different grain boundary segregation states, thus demonstrating the critical role of grain boundary chemistry in the design of solute-stabilized nanocrystalline alloys.